KONSEP PENDIDIKAN LINGKUNGAN HIDUP DALAM PANDANGAN ISLAM - Sulistyo, Agus; Ismarti, Ismarti (Universitas Riau Kepulauan, 2018)
The environmental crisis, known as the ecological crisis, is becoming more widespread. It demands our care as human beings who assume the role of khalifah on earth to actively participate in preventing more massive environmental damage. Man can’t live alone without the support of various resources that exist in his environment. However, the awareness of the importance of preserving and protecting the natural is still lacking. Environmental education is expected to be a vehicle to educate the general public and learners, in particular, to better understand the global environmental crisis phenomenon and foster an attitude to be more concerned with the environment, by internalizing religious values. Building an ecologically-based religious spirit should be conducted simultaneously and sustainably at all levels and compositions of the community especially Muslims, given that the ecological crisis has a universal impact. Recognizing the role of human as a caliph who is in charge of safeguarding and managing nature and the consequences of damaging the environment in terms of Islamic perspective is expected to arouse public awareness to participate actively in maintaining, managing wisely and preserving the surrounding environment. Keywords: environmental ethics; environmental education; conservation; Islam.